2016
DOI: 10.21149/spm.v58i2.7793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of care-delivery delay on the survival of Mexican women with breast cancer

Abstract: Efecto de la demora en la atención sobre la supervivencia de mujeres mexicanas con cáncer de mama. Salud Publica Mex 2016;58:237-250. ResumenObjetivo. Estimar el efecto del tiempo de atención sobre la supervivencia de mujeres con cáncer de mama. Material y métodos. Se realizó el análisis retrospectivo de 854 mujeres atendidas en 11 hospitales entre 2007 y 2009. Se emplearon estimadores de Kaplan-Meier y un modelo de riesgos proporcionales de Cox. Resultados. 10.5% se diagnosticó en etapa I, mientras que 82.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 71 publications
(92 reference statements)
2
22
0
3
Order By: Relevance
“…The main complaint -breast nodule (53% of cases) -and the most common histological subtype -infiltrating ductal carcinoma (85.5% of cases) -are similar to those found in other specialized studies 4,20 . Considering 139 patients who had information on the initial staging, the majority -110 women -were diagnosed with intermediate stages.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The main complaint -breast nodule (53% of cases) -and the most common histological subtype -infiltrating ductal carcinoma (85.5% of cases) -are similar to those found in other specialized studies 4,20 . Considering 139 patients who had information on the initial staging, the majority -110 women -were diagnosed with intermediate stages.…”
Section: Discussionsupporting
confidence: 85%
“…Upon analyzing 73 patients in the state of São Paulo, Trufelli et al 4 reported 17 cases of stage I, 28 cases of stage II, 17 case of stage III and 4 cases of stage IV. In a study by Angeles Llerenas et al 20 , in a Mexican multi-institutional analysis with 854 patients, this distribution was also similar: 88 cases of stage I, 324 cases of stage II, 342 cases of stage III and 62 cases of stage IV.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In Mexico, BC is the most common cause of cancer‐related mortality among women . Although data on the clinical stages of breast cancer are scarce and are not nationally representative, existing studies have reported that 45%–48% of cases are diagnosed in stages III and IV, and only between 10% and 20% in stages 0 and I . In a previous study, both patient delay and health system delay were found to be independently associated with increased probability of advanced BC among Mexican women .…”
Section: Introductionmentioning
confidence: 91%